STRATEGI KEPALA MADRASAH DALAM MENINGKATKAN KUANTITAS DAN KUALITAS PESERTA DIDIK DI MADRASAH TSANAWIYAH MUHAMMADIYAH KOTA SOLOK - abdul malik; Mursal Mursal; Aguswan Aguswan (Ruhama : Islamic Education Journal, 2019)
Abdul Malik, , "The Strategy of Madrasah Heads in Increasing the Quantity and Quality of Students in the Muhammadiyah Islamic Primary School of the City of Solok", Thesis: Islamic Education Study Program, UMSB Padang Postgraduate Program, 2019.This research was motivated by increasing the quantity and quality of students at Solok MTs Muhammadiyah, since the leadership of the Head of the Zulbadri madrasah, SS, which was previously a student in the madrasa, the quantity was small and the quality was low. image The MTs Muhammadiyah in Solok City at that time were runaway schools or exile schools, but nowadays they are superior and competitive schools.This study found (1) the headmaster's constraints in increasing the quantity and quality of students at MTs Muhammadiyah in Solok in the form of lack of facilities and infrastructure, limited financial resources, low quality of students, lack of performance of teachers and education personnel. (2) Evaluation of madrasah principals in increasing the quantity and quality of students at MTs Muhammadiyah in Solok in the form of improved facilities and infrastructure, increased funding sources, improvement of the quality of students, improvement of teacher and education staff performance. (3) The principal's strategy in increasing the quantity and quality of students at MTs Muhammadiyah City of Solok in the form of forming team work, implementing programs to increase the quantity and quality of students, improving the image of madrasas in the community